2019
DOI: 10.1186/s13567-019-0648-9
|View full text |Cite
|
Sign up to set email alerts
|

UBXN1 interacts with the S1 protein of transmissible gastroenteritis coronavirus and plays a role in viral replication

Abstract: Transmissible gastroenteritis coronavirus (TGEV) is an enteropathogenic coronavirus that causes diarrhea in pigs and is associated with high morbidity and mortality in sucking piglets. S1 is one of two protein domains in the spike (S) glycoprotein and is responsible for enteric tropism, sialic acid recognition, and host receptor binding. Although there has been extensive research on the S1 protein of TGEV, little is known about the intracellular role of TGEV-S1. In the present study, we used yeast two-hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…TGEV is an important enteropathogen that causes diarrhea, vomiting, and dehydration in pigs of various ages. To date, host factors, including porcine aminopeptidase N (APN) [32], TRF1 [12], TMEM41B [13], EIF4A2 [14,15], and UBXN1 [14,15], play a positive role in TGEV infection. Moreover, some host protein inhibitors, including the receptor tyrosine kinase inhibitor A9 [16] and the Na+/K+-ATPase inhibitor ouabain [17], can inhibit TGEV infection to various extents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGEV is an important enteropathogen that causes diarrhea, vomiting, and dehydration in pigs of various ages. To date, host factors, including porcine aminopeptidase N (APN) [32], TRF1 [12], TMEM41B [13], EIF4A2 [14,15], and UBXN1 [14,15], play a positive role in TGEV infection. Moreover, some host protein inhibitors, including the receptor tyrosine kinase inhibitor A9 [16] and the Na+/K+-ATPase inhibitor ouabain [17], can inhibit TGEV infection to various extents.…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane protein 41B (TMEM41B) is a host factor required for TGEV replication and contributes to the formation of coronavirus replication organelles [13]. Eukaryotic translation initiation factor 4-alpha (EIF4A2) and UBX domaincontaining protein 1 (UBXN1) play roles in viral replication and can interact with the membrane and spike protein of TGEV, respectively [14,15]. Moreover, increasing studies have indicated that small molecule inhibitors can inhibit TGEV replication by regulating intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Arrdc1 is involved in a variety of processes including cellular protein metabolism, extracellular vesicle biogenesis, and negative regulation of the Notch signaling pathway (30).The down-regulated differential protein AIF1 has been identified as an up-regulated protein of infection (31). The ubiquitin-regulated X (UbX) protein UbXN1, which contains a ubiquitin-associated domain, is a negative regulator of nuclear factor-kB (NF-kB) signaling (32,33). It is suggested that the immune inflammatory response is important in the proteome of septic lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…E protein promotes TGEV maturation in the secretory pathway (65). S1 and M proteins play a role in viral replication (66,67). In addition, M protein can affect TGEV-induced IFN-α production (68).…”
Section: Apoptosis Associated With Transmissible Gastroenteritis Virumentioning
confidence: 99%